SARS-CoV-2 risk factors among symptomatic vaccinated adults attending community testing locations in the Netherlands from June 2021 till February 2022. - Claudia Laarman; Susan J Hahné; Hester E de Melker; Mirjam J Knol (PLoS ONE)
Introduction Most studies on risk factors for a SARS-CoV-2 infection were conducted in the pre-vaccination era with many non-pharmaceutical prevention measures in place. We investigated risk factors for symptomatic SARS-CoV-2 infections in vaccinated persons in a period with a varying degree of prevention measures. Methods In a test-negative case control study among vaccinated adults attending community COVID-19 testing locations between June 1st 2021 till February 28th 2022, we compared symptomatic cases with symptomatic controls (to study risk factors specific for SARS-CoV-2) and with asymptomatic controls (to study risk factors that could apply to respiratory infections in general). We examined potential risk factors including household composition and mitigation behaviour by logistic regression, adjusting for age, sex, and week of testing. Results Risk factors for a positive SARS-CoV-2 test when symptomatic cases were compared to symptomatic controls were: having a household size of more than 4 (adjusted odds ratio: 1.47; 95% CI 1.14-1.92), being a healthcare worker (1.27;1.18-1.47), and visiting busy locations outside (1.49;1.19-1.87). When symptomatic cases were compared to asymptomatic controls, a household size of more than 4 members (1.71;1.25-2.33), living with children aged 0-12 (1.59;1.12-2.26), visiting busy locations outside (1.64;1.24-2.17) were independent risk factors for a positive SARS-CoV-2 test. Risk factors for separate periods and waves differed from the study period as a whole. Conclusion This study was conducted in a period with a varying degree of prevention measures. Among vaccinated individuals, we identified several SARS-CoV-2 specific risk factors and SARS-CoV-2 risk factors that could be more general for respiratory infections. For SARS-CoV-2 transmission more attention could be given to visiting busy outdoor locations, having a household size that consists of more than 4 persons, being a healthcare worker, and living with children aged 0-12. Risk factors varied with different phases in the pandemic, emphasizing the importance of repeated assessment of risk factors.